2006
DOI: 10.1002/ijc.22450
|View full text |Cite
|
Sign up to set email alerts
|

Critical role for matrix metalloproteinase‐9 in platelet‐activating factor‐induced experimental tumor metastasis

Abstract: In this study, the roles of matrix metalloproteinase (MMP)-2 and MMP-9 in platelet-activating factor (PAF)-induced experimental pulmonary metastasis of the murine melanoma cell, B16F10, were investigated. An injection of PAF resulted in increases in mRNA expression, protein levels and the activities of both MMP-2 and MMP-9 in the lungs. The overall expression of MMP-9 was stronger than that of MMP-2. The increased MMP-9 expression was inhibited by both NF-jB and AP-1 inhibitors, whereas the increased MMP-2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
15
0
1
Order By: Relevance
“…MMP-2 and MMP-9 overexpression by pulmonary cells is able to increment the number of lung metastasis in experimental models [54,57]. The increased expression of MMP-9, but not MMP-2, in the lung significantly enhanced the pulmonary metastasis of murine melanoma cells B16F10 [95]. In agreement with this finding the inhibition of the expression of MMP-2 and MMP-9 in the mouse lung reduced lung metastases from B16F10 [96].…”
Section: Lung Metastasissupporting
confidence: 84%
“…MMP-2 and MMP-9 overexpression by pulmonary cells is able to increment the number of lung metastasis in experimental models [54,57]. The increased expression of MMP-9, but not MMP-2, in the lung significantly enhanced the pulmonary metastasis of murine melanoma cells B16F10 [95]. In agreement with this finding the inhibition of the expression of MMP-2 and MMP-9 in the mouse lung reduced lung metastases from B16F10 [96].…”
Section: Lung Metastasissupporting
confidence: 84%
“…This is promising because cathepsins have been shown to increase metastatic potential by facilitating cell migration and invasiveness. The antineoplastic activity of bryostatin-1 has previously been reported in a number of murine and human tumors and cell lines, including breast, lung, and lymphoma [22–23,59]. Thus, our study suggests that the simultaneous induction of immune components in melanoma cells while restricting tumor growth and invasion by bryostatin-1, may contribute to the design of successful chemo-immunotherapeutics against metastatic melanoma.…”
Section: Discussionsupporting
confidence: 70%
“…Most recently, Fallani et al have demonstrated that PAF is being synthesized by B16F10 cells in response to INF-γ treatment, and that PAF promoted the invasion of these cells through the Matrigel-coated filters [110]. Moreover, it has been shown that a single intraperitoneal injection of PAF induced expression of MMP-9 and MMP-2 in the mouse lungs, and significantly enhanced B16F10 pulmonary lung metastasis, suggesting an addition, non-tumor-cell mechanism of PAF action [111]. Finally, in the human melanoma cell line Hs294T, PAFR antagonists were able to prevent adhesion to IL-1-stimulated endothelial cells [112].…”
Section: Paf and Paf Receptor In Melanomamentioning
confidence: 95%